Quantitative ethnobotanical study of wild plant resources of tehsil Utman Khel, District Bajaur, Pakistan - Ali, Adnan; Zeb, Bakht Shah; Khan, Amjad; Haq, Aminul; Haq, Muhammad Abdul; Ullah, Irshad; Badshah, Lal; Zeb, Shaista (Ethnobotany Research and Applications, 2025)
Background: Plants have historically played a vital role in traditional medicine worldwide. This study investigates the quantitative ethnobotanical knowledge of tehsil Utman Khel, District Bajaur, Pakistan. For the first time, it systematically documents the therapeutic and cultural uses of local flora, aiming to preserve this traditional knowledge and explore its potential for modern medicinal applications. Methods: The area's unique flora supports diverse traditional knowledge, particularly in healthcare. Data were collected from 82 local informants through semi-structured questionnaires, field observations, and group discussions. Quantitative analysis was complicated for the Relative Frequency of Citation (RFC), Use Value (UV), and Family Importance Value (FIV) to assess the significance of plant species and families. Results: A total of 88 ethnobotanical species from 48 families were recorded. Leaves and fruits were the most commonly used plant parts due to their availability and ease of use. Herbal remedies were predominantly administered orally (73.86%), with fewer used topically (12.5%) or both ways (13.63%). These remedies treated ailments such as pulmonary infections, gastrointestinal and urogenital disorders, kidney stones, nerve issues, and diabetes. Ajuga integrifolia and Allium cepa were the most significant species based on UV (0.027), while Juglans regia and Mentha arvensis had the highest RFC values (0.28 and 0.19). Among plant families, Lamiaceae had the highest FIV (79.48), followed by Fabaceae (47.62), Apiaceae (46.22) and Asteraceae (43.5). Conclusions: Tehsil Utman Khel possesses rich ethnomedicinal and cultural diversity due to its unique geography and climate. However, this traditional knowledge is at risk of being lost, making its documentation essential for preservation and potential use in modern drug development. Keywords: Wild plants, Relative Frequency Citation, Use Value, Family importance value